PEMBERDAYAAN UMKM DAN PENINGKATAN VALUE ADDED (NILAI TAMBAH) PRODUK TEMPE MELALUI INOVASI OLAHAN TEMPE UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA KEROYA - Akbar, Khaerul; Jaelani, Aenuddin; Alambana, Bondan Muhammad; Athuri, Sofa Selviana; Cahyani, Devi Wahyuni; Arianti, Ria; Maylani, Annisa; Hasanah, Fildzah Azmatun; Riswana, Irya; Suwito, Muhammad Wansyah; Setiawan, Agustono (Universitas Mataram, 2023)
Usaha Mikro, Kecil dan Menengah (UMKM) have an important role in the country's economic development. Even though UMKM make a large contribution and are the backbone of the national economy, they face many problems, including: 1) Not having a business license, 2) Low knowledge on how to run a business, 3) Not using digital marketing to increase sales, 4) Not doing business branding, and 5) Lack of product innovation. This is also a problem UMKM in Keroya Village which makes the community's economy not increase. So it is necessary to empower UMKM and assistance in carrying out product innovations to be able to improve the community's economy. With regard to the description above, an experiment was carried out in innovating processed tempe products, namely making tempeh chocolate. Making this product innovation aims to improve Value Added of tempe products in Keroya Village. It is hoped that through the empowerment of UMKM and innovation of tempeh chocolate products, it can help UMKM in Keroya Village to further develop in the future and the product of tempeh chocolate in Keroya Village can be recognized by the wider community so that it can improve the community's economy.